Surface catalysed PCDD/F formation from precursors - high PCDF yield does not indicate de novo mechanism!. (2017) - Nganai, Shadrack; Lomnicki, Slawo
We report results on PCDD/F formation over iron (III) oxides catalysts for a mixture of 2-monochlorophenol (2-MCP) and 1, 2-dichlorobenzene (1, 2-DCBz) for both oxidation and pyrolysis. Competitive adsorption between chlorinated benzenes and chlorinated phenols affects the transformation of these precursors and plays a crucial role in the PCDD/F formation in mixed MCP/1, 2-DCBz-feed streams. Comparing the integrated PCDD and PCDF yields, it becomes apparent that with decreasing 2-MCP content in the feed stream the PCDF yield first rises and then levels off, at ~0.4% for pyrolytic and at ~0.6% for oxidative conditions. Present results further confirm that the PCDD/PCDF-ratio cannot be used to validate the de novo pathway nor can it be used as an indicator of de novo synthesis in incinerators. In fact, the PCDD/PCDF-ratio is strongly dependent on the relative concentration of these two precursors in the reacting stream, i.e., chlorinated benzenes vs. chlorinated phenols.